Optimizing Participatory Approach through KKN Programs for Empowering Five Pillars in Sukadamai: Optimalisasi Pendekatan Partisipatif melalui Program KKN untuk Pemberdayaan Lima Pilar Desa Sukadamai - Eka Putri Jayanti (Yayasan Cerdas Pedia Indonesia, 2025)
The Community Service Program (KKN) in Sukadamai Village, Cikupa, Tangerang applies a participatory approach to empower five pillars: economy, education, health, religion, and environment. Through preliminary surveys, socialization, and intensive collaboration with village authorities and residents, students designed and implemented digital literacy training for MSMEs, child literacy programs, posyandu activities, religious events, and waste management initiatives. Evaluation revealed enhanced MSME digital capacity, increased children’s reading interest, improved nutritional awareness, social cohesion, and eco-friendly practices. A significant sense of ownership emerged among residents, overcoming time constraints and economic priorities. The synthesis of Participatory Action Research and Asset-Based Community Development principles strengthens contextual relevance. These findings confirm the effectiveness of micro-level participatory interventions in generating sustainable impact in peri-urban areas. Recommendations include establishing a sustainability unit and strategic partnerships for program replication.